Regionalisasi Wakaf Tanah di Provinsi Aceh: Suatu Telaah Pemetaan dan Kebijakan - Hafiizh Maulana; Nurul Iski; Aditya Putra Pratama (AL-MUZARA'AH, 2019)
This research was conduct to identify the regionalization of land waqf in Aceh Province based on compilation of waqf data sourced from Sistem Informasi Wakaf (Siwak) The Ministry of Religious Affairs of the Republic of Indonesia. This research is interesting because there are no studies that have conducted mapping land of waqf. Mapping of potential land waqf in Aceh Province wants to offer an easy solution in terms of inventory potential region as making policy. The methode used by descriptive analysis which is also elaborated with Geographic Information System analysis (GIS) tool. Based on the results of the GIS mapping conducted in the area of land waqf in Aceh Province, land waqf is concentrated in North Aceh District covering 63% of the distribution waqf land in Aceh. However, land Waqf has not been synergy optimally managed with the process of certifying legality. Regionalization needs two types of policy schemes; those are nazhir and waqif perspectives. Nazhir perspective policy is carried out in the scheme of forming professional waqf nazhir institutions. Meanwhile, the waqf perspective policy needs to be carried out with spatial planning and waqf area with the establishment of an Aceh waqf management body regulated in a Perda/Qanun.